The Classroom Teachers Role in Implementing Guidance and Counseling for Children with Aggressive Behavior - Anneke Kynda; Budi Astuti; Alifa Nurul Karima (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Kerinci, 2023)
The class teacher is a teacher in a school who has the task of teaching various subjects. In addition to their duties in providing learning, class teachers also have responsibilities that must be carried out, namely, carrying out guidance and counselling. This study aims to describe the classroom teacher's role in implementing guidance and counselling for mentally disabled children who behave aggressively at a private Special School (SLB) in Sumedang, West Java, Indonesia. This study is a descriptive qualitative research. The subjects in this study were 4 class teachers and 2 parents of students with mental retardation who behaved aggressively. Data collection techniques in this study include observation techniques, interviews and documentation. Data analysis techniques in this study used qualitative data analysis, which consisted of data collection, data reduction, data presentation, and conclusion. The results of this study indicate three role of class teacher in implementing guidance and counselling for mentally disabled children who behave aggressively, namely as an informant, namely providing information related to learning, guidance and counselling as well as the values of life that apply in the social environment; as a facilitator namely facilitating student needs such as understanding student learning skills, providing actions that are following students' interests and talents, facilitating learning facilities and infrastructure; and as a mediator, namely being an intermediary in overcoming learning difficulties and student development problems.